An in vitro Study on the Role of Hepatitis B Virus X Protein C-Terminal Truncation in Liver Disease Development - Siddiqui, Zaheenul Islam; Azam, Syed Ali; Khan, Wajihul Hasan; Afroz, Masarrat; Farooqui, Sabihur Rahman; Amir, Fatima; Azmi, Md Iqbal; Anwer, Ayesha; Khan, Saniya; Mehmankhah, Mahboubeh; Parveen, Shama; Kazim, Syed Naqui (Frontiers in Genetics, 2021)
Hepatitis B virus X protein C-terminal 127 amino acid truncation is often found expressed in hepatocellular carcinoma (HCC) tissue samples. The present in vitro study tried to determine the role of this truncation mutant in the hepatitis B–related liver diseases such as fibrosis, cirrhosis, HCC, and metastasis. HBx gene and its 127 amino acid truncation mutant were cloned in mammalian expression vectors and transfected in human hepatoma cell line. Changes in cell growth/proliferation, cell cycle phase distribution, expression of cell cycle regulatory genes, mitochondrial depolarization, and intracellular reactive oxygen species (ROS) level were analyzed. Green fluorescent protein (GFP)–tagged version of HBx and the truncation mutant were also created and the effects of truncation on HBx intracellular expression pattern and localization were studied. Effect of time lapse on protein expression pattern was also analyzed. The truncation mutant of HBx is more efficient in inducing cell proliferation, and causes more ROS production and less mitochondrial depolarization as compared with wild type (wt) HBx. In addition, gene expression is altered in favor of carcinogenesis in the presence of the truncation mutant. Furthermore, mitochondrial perinuclear aggregation is achieved earlier in the presence of the truncation mutant. Therefore, HBx C-terminal 127 amino acid truncation might be playing important roles in the development of hepatitis B–related liver diseases by inducing cell proliferation, altering gene expression, altering mitochondrial potential, inducing mitochondrial clustering and oxidative stress, and changing HBx expression pattern.